2008
DOI: 10.1007/s11745-007-3142-5
|View full text |Cite
|
Sign up to set email alerts
|

Oral Nanoparticulate Atorvastatin Calcium is More Efficient and Safe in Comparison to Lipicure® in Treating Hyperlipidemia

Abstract: Atorvastatin calcium (AC) is a second-generation 3-hydroxy-3-methylglutaryl-CoA reductase inhibitor approved for clinical use as a lipid lowering agent. AC, the world's best selling drug is associated with poor oral bioavailability and serious adverse effects like rhabdomyolysis on chronic administration. A biodegradable nanoparticulate approach was introduced here with a view to improving the efficacy and safety of AC. Poly lactide-co-glycolic acid (PLGA) nanoparticles containing atorvastatin calcium were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…26 Atorvastatin has pleiotropic effect through insulin sensitization as it reduces the glucose levels to some extent. 5 In the present study, the 10%ATV-LNE and 20%ATV-LNE groups reduced serum glucose levels compared to all groups especially ATV-Sol groups. In contrast, the serum insulin levels showed no significant differences between all studied groups excepting Blank-NE group showed an increase compared to normal and 20% ATV-LNE groups.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…26 Atorvastatin has pleiotropic effect through insulin sensitization as it reduces the glucose levels to some extent. 5 In the present study, the 10%ATV-LNE and 20%ATV-LNE groups reduced serum glucose levels compared to all groups especially ATV-Sol groups. In contrast, the serum insulin levels showed no significant differences between all studied groups excepting Blank-NE group showed an increase compared to normal and 20% ATV-LNE groups.…”
Section: Discussionsupporting
confidence: 51%
“…Meena reported a similar result induced by lipicure nanoparticles formulations. 5 Histopathological examination of kidney from untreated HFD-fed group showed damage of some renal corpuscles and congestion of some glomerular capillaries as well as tubular affection. These findings were supported by those of Ayoub who reported that HFD increased blood glucose, insulin and disturbed the lipid profile.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations